2006
DOI: 10.1111/j.1747-0765.2006.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of iodine in a forest plot, an upland field and a paddy field in the upland area of Tsukuba, Japan: Seasonal variations in iodine concentration in precipitation and soil water and estimation of the annual iodine accumulative amount in soil horizons

Abstract: In the course of a series of studies conducted to investigate the long‐term behavior of 129I (which has a half‐life of 16 million years) in the environment, seasonal variation in the concentration of stable iodine (127I) in precipitation and soil water to a depth of 2.5 m in a forest plot, an upland field and a paddy field in the upland area of Tsukuba, Japan, were determined. Iodine concentration in precipitation tended to increase during the summer (high air temperature) season and low‐rainfall period, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This might suggest that the introduction of iodine into soil with growing plants promotes the formation of iodine compounds that are soluble in 0.03 M acetic acid. Yuita et al (2006) reported an increase in the iodine content in soil during a spring season that was followed by an increase of air temperature and soil humidity after winter.…”
Section: Efficiency Of Iodine Biofortification Of Spinachmentioning
confidence: 96%
“…This might suggest that the introduction of iodine into soil with growing plants promotes the formation of iodine compounds that are soluble in 0.03 M acetic acid. Yuita et al (2006) reported an increase in the iodine content in soil during a spring season that was followed by an increase of air temperature and soil humidity after winter.…”
Section: Efficiency Of Iodine Biofortification Of Spinachmentioning
confidence: 96%
“…The iodine in the groundwater in the Yuchi Formation has three origins: (1) seawater and lagoon water from when the coastal sediment was deposited, (2) infiltrated meteoric water from before 0.04 Ma (corresponding to the 81 Kr age in groundwater at the Upper Yuchi Formation in Table 1 ), and (3) iodine released from organic matter in the sediment. The concentrations of 127 I supplied from meteoric water and seawater are only several µg L -1 (Yuita et al 28 ) and ~ 58 µg L -1 (Elderfield and Truesdale 29 ), respectively. Iodine is easily adsorbed on sediments 30 , 31 and tends to accumulate in organic matter 32 , cells of marine diatoms 33 and humic substances 34 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Johnson (1980) analyzed 183 soil samples from the United Kingdom and found that water-extractable values could be  0.1 mg · kg 1 , representing  0.1% of total soil iodine. Yuita et al ( , 2006 determined concentrations of iodine naturally present in soil solutions of forest, upland, and paddy field soils of Japan. Similarly, Hou et al (2003) found that readily available (the most environmentally mobile) 129 I (water-soluble and exchangeable fractions) accounted for around 20% of total 129 I in Chernobyl soil and around 10% of total 129 I in Irish Sea sediment ( Figure 11.2).…”
Section: Partitioning Of Iodine Into the Liquid Phase Of The Soilmentioning
confidence: 99%
“…Yuita et al (2006) found that drainage of saturated, anoxic paddy field soil led to reduction in iodine concentration of surface soil due to leaching of soluble iodine with the drainage waters. Yuita et al (2006) found that drainage of saturated, anoxic paddy field soil led to reduction in iodine concentration of surface soil due to leaching of soluble iodine with the drainage waters.…”
Section: Migration Of Liquid-phase Iodine Through Soilmentioning
confidence: 99%